Effectiveness of ligation of uterine vessels prior to uterine incision for major placenta previa on reducing maternal morbidity without increasing neonatal morbidity - V. K., Shantha; M., Priyadarshini; Dharshini A., Priya; Jacob, Litty Mariyam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Placenta previa causes massive obstetric haemorrhage and severe maternal morbidity. The objective is to analyse the effectiveness of uterine vessels (artery and vein) ligation before uterine incision in reducing blood loss and hysterectomy during caesarean section for major placenta previa without increasing morbidity in the newborn. Methods: A retrospective analysis of caesarean section for major placenta previa from 2002 to 2017 was done. Uterine vessels ligation before uterine incision was done in 52 patients. In 19 patients unilateral and in 33 patients bilateral uterine vessels ligation was done before uterine incision. In control group, 12 patients with major placenta previa uterine vessels were ligated after the removal of the placenta. The blood loss, blood transfusion, maternal morbidity and NICU admission of the newborns were compared. Results: The mean blood loss was 1002 ml in unilateral, 793 ml in bilateral uterine vessels ligation group, compared to 2191 ml in the control group. The mean blood transfusion volume 0.89 units in unilateral 0.60 units in bilateral ligation group while 2.33 units in the control group. The difference in blood loss and blood transfusion were statistically significant. Out of 52 babies, only 6 babies were admitted in NICU for mild depression with stay less than 3 days. Conclusions: Uterine vessels ligation before uterine incision reduces blood loss and hysterectomy during caesarean section for placenta previa without increasing the morbidity in the newborns.